THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE WORK PRODUCTIVITY IN THE BATAM CITY GOVERNMENT WITH THE WORK ENVIRONMENT AS AN INTERVENING VARIABLE - Syahibul Aziz; Sri Langgeng Ratnasari; Herni Widiyah Nasrul (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This research analyses the influence of leadership style and work motivation on employee productivity in the Government of Batam City (Pemko Batam), considering the work environment as an intervening variable. The methodology used is a mixed approach of qualitative and quantitative methods. For the qualitative approach, in-depth interviews, field observations, and document studies related to the research object were conducted. Meanwhile, for the quantitative approach, a survey was conducted with 250 employees within Pemko Batam, with data collected through questionnaires distributed using purposive sampling. The results show that both qualitative and quantitative approaches have the same correlational results: leadership style significantly affects employee productivity, work motivation has a positive relationship with employee productivity, and the work environment proves to serve as an intervening variable that influences the relationship between leadership style and work motivation with employee productivity in the Government of Batam City.